Non-Formal English Course Towards Students’ Speaking Performance - M. Husni Thamrin; Taufiq Kurniawan (Lencana: Jurnal Inovasi Ilmu Pendidikan, 2023)
This study aimed at developing the learners’ ability of the English language. Seen from the successfulness of one in studying the language, Non-formal English Course has much contribution to the English language teaching. The Non-formal English course is denoted as the enrichment toward the students that is studying English in junior, senior high school and event in the university. This research constitutes casual comparative study with the main objective is the English students at Hamzanwadi University, Lombok, Indonesia. The numbers of accessible population in this study are 40 students who follow and did not follow Non-formal Course of English. Data was collected using semi-structure interview. The result revealed that the mean score of students’ speaking performance who followed Non-formal English was 78.25. It proved students’ speaking performance who followed Non-formal English course was high. However, after calculating the comparison of the students’ speaking performance who follow and do not follow it, the researcher found only 3.55 of t-test which means the degree of comparison between them was high comparison. In conclusion, this analysis found the students’ speaking performance who followed Non-formal English Course and those who did not has high comparison.